Theoretical and experimental investigations of neutral ligand effects in ruthenium-mediated catalysis - Foucault, Heather M (University of Ottawa (Canada), 2006)
The activity of novel ruthenium-hydride complexes RuHCl(CO)(IMes)(PPh 3) and RuHCl(CO)(H2IMes)(PPh3) was screened for the hydrogenation of sterically-hindered trans internal olefins, and compared to known catalysts RuHCl(CO)(PCy3)2 and RuHCl(CO)(IMes)(PCy 3). The presence of a labile ancillary donor (i.e. PPh3) proved to be necessary for the high activity of the N-heterocyclic carbene catalysts. However, where possible, competing isomerization and polymerization reactions occurred on the timescale of hydrogenation. Quantum chemical calculations were performed on model systems RuHCl(CO)(PH 3) and RuHCl(PH3)2 to identify the role of the carbonyl ligand within the context of catalysis. The resulting data did not support the proposal that this ligand's presence activates the resulting catalyst toward hydrogenation of olefins. No net stabilization of the rate-determining step by CO-containing RuHCl(CO)(PH3)2 was observed. The resistance to &sgr;→pi isomzerization afforded by a chelating iminopyrrolato ligand was examined through synthesis of RuCl(&kgr; 2-N,N'-(2,6-iPr2C 6H3)-N=CHC4,H3N)(PPh3) 2]2. Retention of the &sgr;-bound binding mode was confirmed on the basis of solution NMR characterization. Data from one dimenional 31P dipolar chemical shift, and two-dimensional 31P- 31P J-resolved NMR spectra, both of which were gathered in the solid state, confirm that the PPh3 ligands on each metal center are cis-disposed. Data from pulsed field gradient spin echo diffusion NMR experiments establish the dimeric structure of this compound.
Keywords: Chemistry, Physical.